Responses in growth performance and nutrient digestibility to a multi-protease supplementation in amino acid-deficient broiler diets - Cho, Hyun Min; Hong, Jun Sun; Kim, Yu Bin; Nawarathne, Shan Randima; Choi, Inchul; Yi, Young-Joo; Wu, Di; Lee, Hans; Han, Seung Eun; Nam, Ki Taeg; Seoung, Eun Il; Heo, Jung Min (Journal of animal science and technology, 2020)
The present study was conducted to investigate the effect of a multi-protease on production indicators of broiler chickens fed a crude protein and amino acid deficient-diets for 35 days immediately after hatch. A total of 448 one-day-old Ross 308 male broiler chicks were allocated in a completely randomized design into one of eight dietary treatments (positive control [PC], negative control [NC: minus 0.5% from PC, and minus 2% of lysine, methionine, threonine and methionine plus cysteine], extreme negative control [ENC: minus 1% from PC, minus 4% of lysine, methionine, threonine and methionine plus cysteine], and plus multi-protease 150 or 300 g per ton [e. g., PC-150]; PC, PC-150, NC, NC-150, NC-300, ENC, ENC-150, ENC-300) to give eight replicates with seven birds in a battery cage. Body weight, average daily gain, average daily feed intake, feed conversion ratio, and mortality were measured every week. Carcass traits, proximate analysis of breast meat, and ileum digestibility were analyzed on day 21 and 35. Feeding a multi-protease (i.e., more than 150 g/ton) for 35 days immediately after hatching improved feed efficiency and ileum digestibility (i.e., dry matter, crude protein, and energy) compared to their counterparts (i.e., diets without multi-protease: PC, NC, and ENC). In conclusion, our results indicated that broiler chickens fed nutrients deficient-diet (i.e., crude protein and amino acids) supplemented a multi-protease had an ability to compensate and (or) improve their growth performance commensurate with increased ileal digestibility for 35 days immediately after hatch.